The Effect of Corporate Social Responsibility in Achieving Competitive Advantage at Jordanian Supply Chain - Areiqat, Ahmad Yousef; Abdelhadi, Tawfiq Saleh; Abu Rumman, Ayman Ahmad; Al-Bazaiah, Sakher abdrabuh (ExcelingTech, 2019)
The study aimed to identify the effect of social responsibility dimensions in achieving competitive advantages at Jordanian supply chain companies. To achieve the study objectives qualitative study has been conducted, extensive literature review and bibliographic analysis has been conducted, meanwhile, annual reports and secondary data have been collected with reference to the theoretical literature in this field. The studys population consist Jordanian supply chain companies which are: Royal Jordanian Royal Falcon- Royal Wings Fly Jordan Air Arabia Jordan supply chain companies. The collected data were coded for the purpose of analysis. The statistical analysis was used to describe the sample characteristics and to measure the attitudes towards the statements that measure the study independent and dependent variables. After extensive literature it has been found that the major dimensions of social responsible are economical, legal, ethical and philosophical social responsibilities. Analysis indicated that there are no differences of corporate social responsibility effect on achieving the competitive advantage at Jordanian supply chain companies due to companys age, Companys size and Companys number of employees Results also indicated that there are differences effects of corporate social responsibility but not significantly by Companys operational capital. For future research empirical research is recommended to generalize this proposed model.